PEREKONOMIAN DAN PERDAGANGAN PADA MASA PERUNDAGIAN KAJIAN DATA MEGALITIK DI DATARAN TINGGI PASEMAH SUMATERA SELATAN - Indriastuti, Kristantina (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2010)
Economics in the past as the reflections of the economics act such as the activities of food and huntered gathered, fish catching, even farming activities either. To fulfil of their various needs that were also made an exchange activities by barter system. The exchange is the central concept in archaeology, when referring to material goods, to commodities, it’s means much the same as trade. Tradding and economics activitivities that were happened in Pasemah plateau be recognized by the artifacts as the clues of their trading in the past.